[Mn(terpy)Sb2S4]n, a 1D Network of MnSb4S5 Rings Exhibiting a Pronounced Magnetocaloric Effect and Luminescence. Issue 18 (30th April 2020) - Danker, Felix; Anderer, Carolin; Poschmann, Michael; Terraschke, Huayna; Näther, Christian; van Leusen, Jan; Bensch, Wolfgang; Kögerler, Paul
Abstract : The solvothermal reaction of an aqueous solution of Na3 SbS3 or Schlippe's Salt (Na3 SbS4 · 9H2 O) in the presence of Mn(ClO4 )2 · 6H2 O and terpy (terpy = 2, 2':6', 2''‐terpyridine) or the [Mn(terpy)] 2+ complex led to crystallization of the new compound [Mn(terpy)Sb2 S4 ] n (I ). The unique crystal structure of I features chains formed by fused MnSb4 S5 rings. The Mn 2+ cation is coordinated by one terpy ligand and two S 2– anions resulting in a distorted MnN3 S2 trigonal bipyramid. The terpy ligands point to the exterior of the chains, distances between neighbored ligands indicate π··· π stacking. Magnetic investigations show paramagnetic behavior ( µ eff = 5.92 µB /Mn 2+ at room temperature). Field‐dependent magnetic susceptibility measurements at different temperatures evidence a significant magnetocaloric effect of –Δ S = 20.54 J kg –1 K –1 at T = 2 K for a magnetic field change of Δ B = 9 T. The compound exhibits blue luminescence, and a detailed analysis allowed assignment of the emission and excitation bands to the different constituents of the compound. Abstract : A remarkable large magnetocaloric effect is observed for the coordination polymer [Mn(terpy)Sb2 S4 ] n . The compound was prepared under solvothermal conditions with either Na3 SbS3 or Na3 SbS4 · 9H2 O in the presence of [Mn(terpy)2 ](ClO4 )2 or Mn(ClO4 )2 · 6H2 O and terpy. The network topology is unique among all thioantimonate(III)‐containing structures.